DESIGNING OF LEARNING ACTIVITY FOR EXPLICATING NATURE OF SCIENCE - Anggiyani Ratnaningtyas Eka Nugraheni; Chokchai Yuenyong (Universitas Negeri Yogyakarta, 2020)
This study was aimed at clarifying the learning activities for explicit Nature of Science (NOS) which provide through context based STS (Science, Technology, Society) learning approach. The study followed the 4-D procedure but in this article only was presented up to the third step. These steps included define, design, and develop. The data were gathered through expert judgment by chemistry educator for product revision. The views of the chemistry teacher were explored through a closed-questionnaire that was analyzed by percentage. One of learning activity plan have arranged. The learning activity with context based STS approach consists of 5 stages including identification of social issues/history, identification of potential solution, need for knowledge, decision-making, and socialization and completion decision stage. Chemistry teachers’ view toward the feasibility of learning activity plan was good. The learning activity was developed with topic a history of the Father of Modern Chemistry for grade 10th. The findings show thatt his learning activity is able to help teacher for teaching NOS in classroom and foster students’ NOS through a historical story.